Orthodontic digital workflow: devices and clinical applications - Taís de Morais Alves da CUNHA; Inessa da Silva BARBOSA; Karolinne Kaila PALMA (Dental Press Editora, 2021)
ABSTRACT Introduction: The digital technology has contributed to improve and simplify diagnosis, treatment planning and execution in Orthodontics. Among CAD/CAM system (Computer-Aided Design / Computer-Aided Manufacturing) applications in Orthodontics, we highlight the installation and removal of fixed appliance, clear aligners, customized appliances, and retainers fabricated in digital environment. This approach has several advantages for practitioner and patient, as it enhances appliances precision, directly interferes in treatment time and predictability. Even with all the benefits arising from the digital workflow, few orthodontists have adopted this technique in their clinical practice, most due to high cost and lack of technical preparation for proper execution. Objectives: Thus, given the importance of digital technology to improve specialty performance and the still incipient incorporation of digital flow in Orthodontics, the purpose of this article is to describe the available resources and clinical applications of the CAD/CAM technology in Orthodontics.